pusat promosi, penjualan dan pemasaran hasil hortikultura di karawang jawa barat - Imas Ririan; Sri Kurniasih (MAESTRO, 2019)
Abstract Center for Promotion and Marketing of Horticultural Products in Karawang, West Java is a container for the sale of agricultural products of West Java residents in the field of Horticulture in particular. As one of the city facilities, the Neo Vernacular concept approach with raised cultural elements can be an added value in the community's interest in using city facilities, to facilitate local communities in their activities. At present, Karawang does not have a Horticultural sales container, so the establishment of a Horticultural Product Promotion, Sales and Marketing Center will be able to generate or increase Horticultural sales in the West Java region. Neo Vernacular concept is widely used for building design, such as government buildings and markets, because Neo Vernacular does not merely raise modern elements but also gives a touch of local culture. Keywords : Neo Vernacular, Karawang Center for Promotion, Sales, and Marketing of Horticultural Products